2002
DOI: 10.1067/mva.2002.120373
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of acute mesenteric ischemia: Factors associated with survival

Abstract: The contemporary management of AMI with revascularization with open surgical techniques, resection of nonviable bowel, and liberal use of second-look procedures results in the early survival of two thirds of the patients with embolism and thrombosis. Older patients, those who did not undergo bowel resection, and those with NMI have the highest mortality rates. The long-term survival rate remains dismal. Timely revascularization in patients who are symptomatic with chronic mesenteric ischemia should be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
274
10
36

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(345 citation statements)
references
References 27 publications
16
274
10
36
Order By: Relevance
“…As might be expected, most of these patients have comorbidities, the most commonly reported being hypertension [10,11], which is present in more than 70 %. Other common associated conditions include coronary artery disease, chronic renal failure, diabetes, peripheral vascular disease, cerebrovascular disease and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As might be expected, most of these patients have comorbidities, the most commonly reported being hypertension [10,11], which is present in more than 70 %. Other common associated conditions include coronary artery disease, chronic renal failure, diabetes, peripheral vascular disease, cerebrovascular disease and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 93%
“…One study [10] reported multiorgan failure to be the most common cause (75 %) of death in these patients, the others being rethrombosis, myocardial infarction and obstructive pulmonary disease. Similarly, we found multiorgan failure to be the cause of mortality in 28 of our patients (61 %) with septicaemia in 16 patients, only 8 of which were from an identifiable source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os sintomas mais comuns, segundo estudo de Park e cols. 2 , são dor abdominal (95% dos pacientes), seguida de náuseas em 44% dos pacientes. Diarréia com sangue ou hematoquezia estão presentes em 16% dos pacientes, mas enterorragia maciça é incomum.…”
Section: Aspectos Clínicosunclassified